Empires between Islam and Christianity, 1500-1800 - Subrahmanyam, Sanjay (SUNY series in Hindu studies, 2019)
"Empires between Islam and Christianity uses the innovative approach of "connected histories" to address a series of questions regarding the early modern world in the Indian Ocean, the Mediterranean, and the Atlantic. The period between 1500 and 1800 was one of intense inter-imperial competition involving the Iberians, the Ottomans, the Mughals, the British, and other actors. Rather than understand these imperial entities separately, Sanjay Subrahmanyam reads their archives and texts together to show unexpected connections and refractions. He further proposes, in this set of closely argued studies, that these empires often borrowed from each other, or built their projects with knowledge of other competing visions of empire. The emphasis on connections is also crucial for an understanding of how a variety of genres of imperial and global history-writing developed in the early modern world. The book moves creatively between political, economic, intellectual, and cultural themes to suggest a fresh geographical conception for the epoch"--